Model Pembelajaran Kooperatif Tipe Stad dengan Menggunakan Kartu Domino pada Materi Trigonometri - Nazariah; Nashrullah Mailisman; Cut Mawar Helmanda; Ilham Wahyudi (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2026)
An abstract is a brief summary of a research article, review, or any-depth analysis of a particular subject or disipline, and is often used to help the readers understand the paper purposes. an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper.